Evaluation of airfield pavement micro and macrotexture in the light of skid resistance (friction coefficient) measurements - Wesołowski, Mariusz; Blacha, Krzysztof (MATEC web of conferences, 2019)
Appropriate skid resistance properties of airfield pavements are extremely important in terms of the safety of air operations. When discussing skid resistance properties of airfield pavements, we should not limit the subject only to the friction coefficient, which determines the state of its roughness. Attention should be paid to the fact that a significant component of friction characteristics of a tyre/pavement contact surface is the pavement texture (microtexture and macrotexture). The authors of the article presented the currently applied study methods in the scope of evaluating the texture of road and airfield pavements. The paper also presents sample results of field tests, which were conducted on new airfield pavements (executed in the cement concrete and asphalt concrete technology), as well as their short analysis in relation to evaluating the skid resistance properties (friction coefficient). Particular attention was paid to the current requirements in this scope, imposed on airfield pavements and the assessment criteria of the obtained results. Moreover, the paper also presents a direction of further works conducted by the authors with a broader team, in the scope of developing the study method for the assessment of airfield pavement texture.